2017
DOI: 10.4081/ejh.2017.2833
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegeneration in zebrafish embryos and adults after cadmium exposure

Abstract: Cadmium is a biologically non-essential metal. It is also toxic to many organs including the brain. The aim of this study was to analyse the neurodegenerative effects of this metal in embryos and adults of zebrafish exposed to sub-lethal concentrations of cadmium. The study was performed by cytochemical stainings. Six hours post fertilisation (hpf) zebrafish embryos were treated for 24 hours with 9 μM of cadmium and subsequently stained with Acridine orange in whole mount to detect apoptosis in the brain. Adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…In this study, 24 h exposure of Cd exhibited alteration of oxidative stress markers (Cu/Zn-SOD, CAT, and iNOS) and brain inflammatory markers (COX-2, NF-κB, Keep1, COX-2) at all transcription, translation, and post-translation levels [175]. In line with similar results, Cd had also reported altering brain (glial and neuronal cells) and mitochondrial morphology in zebrafish on incubation at a lower dose [176,177]. Cadmium induced oxidative stress may damage brain lipids and protein, but it's interesting to observe that a well-known toxicant like chlorpyrifos has acted like an antagonistic to Cd [178].…”
Section: Cadmium (Cd)supporting
confidence: 87%
“…In this study, 24 h exposure of Cd exhibited alteration of oxidative stress markers (Cu/Zn-SOD, CAT, and iNOS) and brain inflammatory markers (COX-2, NF-κB, Keep1, COX-2) at all transcription, translation, and post-translation levels [175]. In line with similar results, Cd had also reported altering brain (glial and neuronal cells) and mitochondrial morphology in zebrafish on incubation at a lower dose [176,177]. Cadmium induced oxidative stress may damage brain lipids and protein, but it's interesting to observe that a well-known toxicant like chlorpyrifos has acted like an antagonistic to Cd [178].…”
Section: Cadmium (Cd)supporting
confidence: 87%
“…It is reported that long‐term exposure (from days to weeks) to certain metals, including Cd, affects several processes and behaviors (LeFauve & Connaughton, 2017; Monaco et al., 2017) including swimming abilities in developing larvae (Capriello et al., 2019). On another hand, brief Cd exposure (up to 3 hr) during embryonic development can inhibit specifically the olfactory system, leading to the activation of cell death pathways in the larval olfactory epithelium (Blechinger et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Cadmium (Cd) exposure produces significant olfactory epithelium alterations, including reduction in OSNs and disruption in olfactory epithelium neurogenesis, through an increase in the generation of reactive oxygen species. These olfactory alterations correlate with a long-term decrease in alarm and avoidance responses [88,114,115,116,117,118,119]. Exposure to Copper (Cu) causes marked OSN death, with a preferential loss of ciliated in comparison to microvillous OSNs; impairs the transcription of a wide variety of genes involved in olfactory processing, such as ORs and ionic channels; and reduces the recognition of bile salts while impairing odor-mediated alarm responses [120,121,122,123,124].…”
Section: The Olfactory System Of Zebrafish As a Model Of Neuroplasmentioning
confidence: 99%